PENGARUH PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE BERBASIS TANYA JAWAB TERHADAP KEMAMPUAN MENGANALISIS MATERI SEJARAH SISWA KELAS X IPS MAN 1 LAMPUNG TIMUR - Eka Cahayati; Sumiyatun Sumiyatun (Swarnadwipa, 2017)
This study was conducted to determine the effect of Word Square-based learning model debriefing on the ability to analyze the material history of class X IPS MAN 1 Lampung Timur in academic 2016/2017. This type of research is quasi experiment (quasi exsperiment) type pretest-posttest control group design. The population in this study were all students of class X IPS second semester MAN 1 Lampung Timur in academic 2016/2017, to determine the grade samples researchers used sampling methods cluster random sampling. Thus, in this study the researchers chose a random class in the sampling. Thus, the class X IPS2 obtained by the number of students tested 35 as a class, a class X student IPS3 number 35 as the control class, and a class X student IPS4 with the number 36 as the experimental class. Based on the research process can be concluded that there is a positive effect from the use of influence Word Square-based learning model debriefing on the ability to analyze the material history of class X IPS MAN 1 Lampung Timur in academic 2016/2017.